The evaluation of the nutritional habits of 14-25 years old people with skin problems - Sökülmez Kaya, Pınar; Asal Ulus, Canan; Taşcı, Bahtinur (Progress in Nutrition, 2020)
Objective: To investigate the nutritional habits of the 14-25 years old people with skin problems. Design: We performed a cross-sectional study with random sampling of participants. Skin problems was questioned with questionnaire form. Last three days food consumption was recorded and food consumption frequencies were questioned. Also anthropometric measurements were taken. Setting: A state university and two high school in Samsun, Turkey. Subjects: Students (n =400 ) aged between 14-25 years. Results: Among students, 251 were women and 149 men. 219 of them have skin problems and 181 didn’t have any skin problems. Mean BMI (body mass index) of students was 20.95±2.67 kg/ in women and 22.65±3.17 kg/ in men. Mean body mass index in students with skin problem (SP) was 21.55 ± 2.91 kg/m2 and without SP was 21.61±3.07 kg/. Among students who have SP problems (n = 219), acne (35.2%) was the first skin problem. Gender, sleep duration, physical activity, frequency of eating out, consumption of tea with food, french fries consumption, daily water intake amount had a significant difference on skin problems (p<0.05). More skin problems were found in individuals eating patisseries (p<0.05). Those who not have skin problems were found to consume more milk, yogurt, buttermilk and mineral water (p<0.05). Conclusions: In this study, it was showed that skin problems could be affected by environmental and personal properties. In order to establish a relationship between these problems and nutrition these properties should be examined. There is not enough research on this subject and another randomized controlled trials are needed to determine the relationship.